(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Ways to improve the effectiveness of the class leader’s educational activities, to have a conscious attitude to academic work and to be responsible for it approach, improving the quality of students’ knowledge and establishing discipline in the classroom is highlighted.